RAPD AND SSR BASED GENETIC DIVERSITY ANALYSIS OF ELITE-2 SET OF SYNTHETIC HEXAPLOID WHEATS - Ahmad, Kafeel (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Synthetic hexaploid wheats are artificially reconstituted hexaploid wheats that possess high genetic variation which could be utilized for the development of new improved wheat varieties. One such group of synthetic wheats is called the Elite-II set of synthetic wheats that are derived from crossing durum wheat with different Aegilops tauschii wheats. Materials and Methods: In the current study genetic diversity was investigated among 18 Elite-II synthetic hexaploid wheat lines at DNA level. Two types of molecular markers i.e. RAPD and SSR were used for this purpose. Results: Both types of markers proved useful in estimating the overall genetic diversity among these lines. Based on RAPD data range of genetic distances in these lines was from 0 to 100 percent. Seven D- genome specific SSRs were also used to get further estimation of the genetic diversity contributed by Aegilops tauschii parent. On the basis of results obtained it is inferred that the Aegilops tauschi accessions used in the production of these synthetic lines were genetically different and they contributed to the enhancement of genetic variation in the synthetic lines. These results could be helpful for future genome mapping programs. Conclusion: The overall extensive genitive diversity indicates that these lines are good candidates for development of improved wheat varieties by crossing with cultivated wheat varieties.